2019
DOI: 10.3389/feduc.2019.00029
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Educational Support for Children With Developmental Language Disorder or Autism Spectrum Disorder: Needs, or Diagnostic Category?

Abstract: by diagnostic category limits the possibility of providing effective provision to meet the children's individual language and learning needs. This raises serious questions about the allocation of support resources and, by corollary, indicates the likelihood currently of an inequitable allocation of support to children and young people with DLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 53 publications
0
19
1
Order By: Relevance
“…In addition, although the current study examined for the first time several factors that may explain individual differences in each group related to the impact of COVID-19 on anxiety and worries, it was not possible to examine differences related to the primary diagnosis of the individuals with SEND because uneven groups were recruited and 70% of the individuals with SEND had one of the following developmental disorders: autism, Down syndrome or Williams syndrome, and some conditions were under-represented (e.g., socio-emotional and behavioral difficulties). However, previous studies that have examined outcomes in those with SEND have shown that categorical labels may not be informative with regards to the needs of the individual with SEND (Dockrell et al, 2019 ). Instead, examination of individual differences such as pre-existing health and anxiety diagnoses might be a more useful approach to examine those most affected or in need.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although the current study examined for the first time several factors that may explain individual differences in each group related to the impact of COVID-19 on anxiety and worries, it was not possible to examine differences related to the primary diagnosis of the individuals with SEND because uneven groups were recruited and 70% of the individuals with SEND had one of the following developmental disorders: autism, Down syndrome or Williams syndrome, and some conditions were under-represented (e.g., socio-emotional and behavioral difficulties). However, previous studies that have examined outcomes in those with SEND have shown that categorical labels may not be informative with regards to the needs of the individual with SEND (Dockrell et al, 2019 ). Instead, examination of individual differences such as pre-existing health and anxiety diagnoses might be a more useful approach to examine those most affected or in need.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, the Warnock report discussed prevalence with respect to two levels of severity, evidence now demonstrates a much more complex picture with prevalence varying in relation to type of SEN, age, gender, and ethnicity, as well as socioeconomic disadvantage; and these factors interrelate. In addition to this demonstration of complexity, these data, together with the evidence of more resources proportionately going to children with ASD (than children with SLCN: Dockrell et al, 2019) and more research funding proportionately supporting more research going to ASD than to other neurodevelopmental disorders (Bishop, 2010), there are indications of inequity.…”
Section: Discussionmentioning
confidence: 93%
“…behavioral difficulties). However, previous studies that have examined outcomes in those with SEND have shown that categorical labels may not be informative with regards to the needs of the individual with SEND (Dockrell et al, 2019). Instead, examination of individual differences such as pre-existing health and anxiety diagnoses might be a more useful approach to examine those most affected or in need.…”
Section: Limitations and Future Studiesmentioning
confidence: 99%